Factors That Affect High Blood Cholesterol Levels in Public Health Students Class of 2024 Gorontalo State University - Hikmah Ainun Ahmad; Sirajuddien Bialangi; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Cardiovascular diseases are a group of non-communicable diseases that are one of the main health problems in the world. One of the main risk factors is high cholesterol levels. According to the World Health Organization, cardiovascular disease causes about 17.9 million deaths each year out of the total global deaths. In Indonesia, based on Riskesdas 2018, around 28.8% of the population aged ≥15 years have high cholesterol levels. The Gorontalo City Health Office in 2025 reported 81 cases of coronary heart disease, 3,069 cases of hypertension, and 63 cases of stroke related to high cholesterol. In addition, lifestyle changes such as skipping breakfast, excessive use of gadgets, consumption of Ultra Processed Foods, and poor sleep quality are thought to affect cholesterol levels in the blood. This study aims to analyze the factors that affect cholesterol levels in Public Health students of the 2024 batch of Gorontalo State University. An observational analytical method with a cross-sectional design was carried out at Gorontalo State University on 83 respondents selected through accidental sampling. Data were collected through questionnaires and portable cholesterol checkers, and then analyzed univariate and bivariate using chi-square test (p=0.05). The results showed that there was no association between breakfast habits (p=0.338) and gadget use (p=0.101) and high cholesterol levels. There was a relationship between the consumption of Ultra Processed Food (p=0.001) and sleep quality (p=0.018) with high cholesterol levels in public health students of the class of 2024. Ultra Processed Food consumption and sleep quality were related to cholesterol levels, while breakfast habits and gadget use were not related. It is recommended to maintain a balanced diet, limit Ultra Processed Foods, improve sleep quality, and implement an active lifestyle to prevent increased cholesterol levels and non-communicable diseases.